Todos os nomes, e a descoberta das invenções diárias: livros de artista como registros de narrativas na arte contemporânea - Andrade, Luana de Oliveira (2015)
In this thesis I present my poetic trajectory in two years linked to Todos os nomes (SARAMAGO, 1997), novel which addresses weavings of political issues between the problematizations of the subjects and their inventive powers. The art courses are beyond the comprehension of bureaucracies, here I present my current idea of art reflected in poetic actions experiencing artist books, objects, texts, illustrations, records, happenings and performances. This work is a narrative of intertext between the investigation of the character José and mine. Why be an artist? From this story, I investigated art as a form of re-creation of realities, not without dominions, but finding possible deviations. As theoretical contribution of this research I used: Hutcheon (1991) and Bourriaud (2009) about the postmodern poetic strategies; also Foucault (1998, 2011) to weave relations between the content of this narrative and reflections about power, hierarchies and speeches; besides, Silveira (2001) and Gonzalez (2013) to clarify about the artist book.